De damnabili ritu Graecorum: Osualdus de Lasko’s Sermons Regarding Orthodox Christians in Late Medieval Hungary. - Cotoi, Paula (Medieval Sermon Studies, 2023)
Among the various inhabitants of the Hungarian Kingdom during the Middle Ages, there were also Orthodox Christians, frequently designated as schismatici. Secular and ecclesiastic authorities often sought their conversion and the mission of the Order of Friars Minor in this area targeted them as well. A change of attitude was imposed, at least for a time, in 1439 by the decree of union agreed at the Council of Florence (1438–39). A half a century later, Osualdus de Lasko (c. 1450– 1511), a Hungarian Observant Franciscan, wrote a Lenten homiletic cycle exhorting a profound commitment to the true faith by addressing the question of the Byzantine rite in three of his sermons. This article offers an analysis of the sermon collection entitled Quadragesimale Gemma fidei, focusing mainly on the three sermons de damnabili ritu Graecorum. I will argue that, on a spiritual level, Osualdus intended to strengthen the faith of the Catholic inhabitants of Hungary, to resist and correct deviances, in order to regain God’s mercy. On a temporal level, he promoted the return of the ‘Greeks’ to communion with the Roman Church, through conversion, probably in the interest of a stronger front against the Ottomans.